GENESIS VULKANIK DAKAH BERUMUR TERSIER DI DAERAH KARANGSAMBUNG, KEBUMEN, JAWA TENGAH - Imam Setiawan, Nugroho
The presence of Tertiary volcanic in the Karangsambung area are shallow intrusion of diabas and basalt andesitic, massive lava basaltic, pillow lava basaltic, pyroclastic tuff and hialoclastit breccia in situ and sedimentary. Field observations show that the shallow intrusions were formed in submarine environment consists of volcanic neck in the area of Mount Parang and Mount Bujil, dikes in the area of Jebug River-Banjarsari and Jembling-Kayen River. Petrographic analysis was conducted on 40 samples of volcanic rocks and sedimentary rocks of Tertiary age that have a younger or older stratigraphy relationship in geological age with Tertiary volcanic rocks. Based on the results of petrographic analysis, Tertiary age volcanic igneous rocks that were found in this area have main mineral composition of plagioclase, clinopiroxene and opaque minerals. Olivine is almost not observed in thin sections of igneous rocks. Textures which are common in intrusion diabas are holocristalline, ophitic and subophitic. Basalt andesitic intrusions at Mount Bujil show texture holocristalline, porphiritic and intergranular. Basaltic lava with massive and pillow structure has texture of the hypocristalline, porphiritic, trachitic and intergranular. From the analysis, it can be concluded that in the Tertiary igneous rocks around the Dakah village can be classified of tholeiite. Most of igneous Tertiary rocks had experienced weathering characterized by the presence of brownish-green chloriterich Fe. Others common secondary minerals are present natrolite and calcite that fills the voids in the rock. Attendance natrolite was associated with marine sediments indicate that these rocks had changed experienced in the marine environment. Generally, all of the Tertiary igneous rocks had been experienced strong microtectonic deformation characterized by the bending effect on crystal. Geochemical analysis of major elements and trace elements by XRF method has been carried out on five samples of rock that consists of four diabas and one basaltic andesite and using three data comparison of Tertiary age volcanic rocks in the area of Karangsambung. Based on the analysis results, a set of Tertiary age volcanic rocks in the Karangsambung area is derived from the same magma (co genetic). Thus have affinity of island arc tholeiite based on the plot of discriminant diagrams showing the trace element enrichment in incompatible elements with low ion potential (LIL) (Sr, K, Rb, Ba ± Th) and relatively poor in elements with high ionic potential (HFS) (Ta, Nb, Ce, P, Zr, Hf, Sm, Ti, Y, Yb, Sc and Cr) and the low value of the Ni element. Based on the analysis magma evolution diagram, the eruption center was estimated to be around the Dakah Village consecutive after it was diabas dikes in Jembling-Kayen River, diabas volcanic necks in Mount Parang, diabas dikes in Jebug River-Banjarsari, and basalt andesitic volcanic necks in Mount Bujil at Late Eocene. Island arc tholeiite affinities were formed due to subduction of oceanic plates with oceanic plates. Karangsambung and Totogan Formation considered as an olisostrome which were deposited in the trench with accretion complex basin bedrock associated with the Pre-Tertiary subduction system. The presence of an island arc tholeiite volcanism in melange sedimentary environments of Karangsambung and Totogan Formation provided important tectonics implications on the Karangsambung area. New subduction system occurred in the south of the old Pre-Tertiary subduction. Pre-Tertiary subduction cessation caused by the collision of Gondwanaland microcontinen at the edge of east and southeast Sundaland on Late Cretaceous. Meanwhile the Indo-Australian oceanic plate continues moved toward the North and caused of new subduction path from south of the old Pre-Tertiary subduction. New subduction in the south of Karangsambung expected begins to form at Middle Eocene and the magmatism happened to form the volcanism in the Karangsambung area at Late Eocene. Therefore we can conclude that the presences of the Tertiary volcanic in Karangsambung area were in situ product of volcanism.